Design and experiment of pneumatic pressure control device for no-till planter - Cao, Xinpeng; Wang, Qingjie; Li, Hongwen; He, Jin; Lu, Caiyun; Xu, Dijuan; Wang, Xiuhong (International Journal of Agricultural and Biological Engineering, 2023)
An adequate and uniform press wheel pressure is crucial for the homogeneous development of a crop, as it affects actual seeding depth and germination rate. The problems of uneven compaction of seed furrow and consistency of seeding depth can be caused by the pressure fluctuation of the coil-spring pressure control device (CPCD) when the no-till planter is working on the unplowed ground. In this study, a pneumatic pressure control device (PPCD) was designed for the no-till planter, the key structural parameters of air spring for press wheel pressure (PWP) stability were determined by theoretical analysis and parameter calculation. Using the gas-structure coupling finite element simulation method (FESM), the piston radius, piston angle, and cord angle of the air spring are selected as the test factors, and the vertical stiffness was used as the test index to carry out the quadratic rotation orthogonal combination test to establish the regression model of test index and factor. The bench test of the PPCD was carried out under the optimal parameter combination, piston radius of 27.2 mm, piston angle of 11.7°, and cord angle of 30.0°. The vertical stiffness verification test showed that the simulation test was consistent with the bench test result, the vertical stiffness simulation error was 7.1%, and the internal air pressure simulation error was 3.0%; The control response test showed that the average response time of the air spring inflating and deflating was 0.80 s, the maximum overshoot was 4.33% during inflation, and no pressure overshoot during deflation; Under the condition of –40-40 mm surface relief height, the PPCD could effectively reduce the pressure fluctuation compared with the CPCD, and the average reduction of the pressure fluctuation was about 25.1%. Keywords: air spring, no-till planter, pressure control, finite element analysis DOI: 10.25165/j.ijabe.20231603.7670 Citation: Cao X P, Wang Q J, Li H W, He J, Lu C Y, Xu D J, et al. Design and experiment of pneumatic pressure control device for no-till planter. Int J Agric & Biol Eng, 2023; 16(3): 37–46.